Developmental programming of oxytocin through variation in early-life stress: Four meta-analyses and a theoretical reinterpretation. (June 2021) - Ellis, Bruce J.; Horn, Alexander J.; Carter, C. Sue; van IJzendoorn, Marinus H.; Bakermans-Kranenburg, Marian J.
Abstract: Despite evidence supporting a role for oxytocin (OT) in regulating social behavior, surprisingly little is known about how this neuropeptide is calibrated during development. We systematically reviewed empirical studies in humans ( k = 86 publications reporting on 66 independent samples; N = 7319) that examined associations between early-life stress and three OT system components: endogenous OT, methylation of the OT receptor gene ( OXTRm ), and biological and behavioral responses to intranasally administered OT. In a series of meta-analyses, we found some evidence that people who grew up under more adverse conditions tend to have lower endogenous OT (children: r = .12; adults: r = .09), that early adversity is associated with higher levels of OXTRm ( r = .02), and that adults who report lower levels of childhood adversity tend to show more positive responses to intranasally administered OT ( r = .12). These results were found in typical populations, and were in most cases absent in clinical samples. We discuss these findings in terms of both the prevailing medical model (focusing on the harmful effects of early-life stress) and the adaptive calibration model (focusing on developmental adaptation of biobehavioral systems to early conditions) and suggest that an adaptation-based approach could meaningfully advance research and intervention on the sequelae of early adversity. Highlights: Childhood adversity predicts lower basal OT, higher methylation of the OT receptor gene, and a dampened response to exogenous OT. Adverse early experiences may prepare individuals for later adaptation to harsh environments by calibrating their OT system. Labeling low OT in challenging settings as dysregulated ignores the functional significance of variations in the OT system. Prevention, intervention, and therapy targeting only OT levels risk failing people who have experienced the most severe adversities. Because OT adaptively calibrates to context, individuals as well as environments are potential targets of prevention and treatment.